Perlindungan Hukum Korban Kekerasan dalam Rumah Tangga di Wilayah Hukum Kepolisian Resort Batanghari - M. Rudi Hartono; Ryan Aditama; Ananda Rizky Putra (Wajah Hukum, 2023)
Domestic Violence (KDRT) as a form of violence in a household environment that relies on the gender of women as victims who suffer and suffer as a result of these acts of violence which are generally perpetrated by husbands. In this study, the authors refer to the Analytical Descriptive method, namely solving problems based on data or facts collected as they were at the time the research was carried out, and using the Purposive Sampling method, namely the sample used is based on the subjective views of the research, the respondents were determined by the researcher to represent all population. Based on the research, it is concluded that patriarchal culture is a factor in the emergence of domestic violence, which has the view that a man has a more dominant position in the household which cannot be equated with women and this has the same socio-cultural views. by the Indonesian people. Domestic Violence (KDRT) is seen as a personal problem, because due to private issues it should be socialized in accordance with the provisions of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This study aims to gain a deeper understanding of the factors that cause domestic violence in the jurisdiction of the Batanghari resort police, efforts to resolve crimes and obstacles found in the process of resolving domestic violence crimes. The research method used is empirical research with the type of case study research. Methods of data collection using interviews. The conclusion of this study is that domestic violence occurs because the perpetrator feels that there is annoyance and anger at his wife who often scolds the perpetrator as a husband, so that the perpetrator commits domestic violence to his wife. The way to resolve this case is to do it with peace efforts of both parties.